Value chain analysis of information services for visually impaired people: a case study of contemporary technological solutions. Issue 2 (19th October 2020) - Cheung, Tak Yee; Ye, Zengyu; Chiu, Dickson K.W.
Abstract : Purpose: People with visual impairment comprise the second high disability population in Hong Kong, but only two existing information centers provide information services for visually impaired people, which is inadequate. Therefore, this study aims to provide a more in-depth understanding of the information services for visually impaired people in Hong Kong. Design/methodology/approach: People with visual impairment comprise the second high disability population in Hong Kong, but only two existing information centers provide information services for visually impaired people, which is inadequate. Therefore, this study aims to provide a more in-depth understanding of the information services for visually impaired people in Hong Kong. Findings: IAC's main problems include limited collection, inconsistent multiple digital platforms for user access, limited service hours and limited promotion. Some technological suggestions were proposed, which include: expanding its electronic and special collections, establishing a one-stop digital platform, AI-based chatbot for automated caring chats and reference services, and extending its social network marketing. Originality/value: Scant studies focus on the information services and management of special libraries for visually impaired people, especially in East Asia. On the other hand, there are limited case studies analyzing libraries with value-chain analysis.